A numerical approach for estimating the effective elastic properties of honeycomb structures - Kien, Nguyen Trung; Minh, Nguyen Anh (Vietnam Journal of Mechanics, 2015)
This paper presents a method for calculating effective elastic moduli of honeycomb core of sandwich plates. The theory is based on the homogenization method for periodic composite materials. Abaqus software is used to model the localization elastic problem on a representative volume element and then the balance of micro-macroscopic deformation energy enables to calculate homogenized elastic moduli of the honeycomb core. Numerical examples are carried out and compared to other models.